2009
DOI: 10.1124/jpet.109.161927
|View full text |Cite
|
Sign up to set email alerts
|

Two Flavonolignans from Milk Thistle (Silybum marianum) Inhibit CYP2C9-Mediated Warfarin Metabolism at Clinically Achievable Concentrations

Abstract: Milk thistle (Silybum marianum) is a popular herbal product used for hepatoprotection and chemoprevention. Two commercially available formulations are the crude extract, silymarin, and the semipurified product, silibinin. Silymarin consists of at least seven flavonolignans, of which the most prevalent are the diastereoisomers silybin A and silybin B; silibinin consists only of silybin A and silybin B. Based on a recent clinical study showing an interaction between a silymarin product and the CYP2C9 substrate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 29 publications
(37 reference statements)
2
70
0
Order By: Relevance
“…Both silymarin and silibinin undergo extensive first-pass metabolism in the liver. 37 The nanodroplets containing oils and emulsifiers can be incorporated with lipoproteins and chylomicrons in the intestine. Such mixtures are largely taken up via the lymphatics, thus minimizing the first-pass effect.…”
mentioning
confidence: 99%
“…Both silymarin and silibinin undergo extensive first-pass metabolism in the liver. 37 The nanodroplets containing oils and emulsifiers can be incorporated with lipoproteins and chylomicrons in the intestine. Such mixtures are largely taken up via the lymphatics, thus minimizing the first-pass effect.…”
mentioning
confidence: 99%
“…In a study by Gurley et al (2006), [89] insignificant changes in the disposition of digoxin were observed on co-administration with silymarin, posing no clinically significant risk for P-gp-mediated herb-drug interactions. On the other hand, a study has shown that silybin A and silybin B at clinically relevant concentrations inhibit CYP 2C9-mediated metabolism of warfarin [90]. This HDI needs to be further evaluated because of the narrow therapeutic index of warfarin.…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Despite the apparent ability of milk thistle extracts to produce significant inhibition of one or more P450 enzymes, as reported in several published in vitro studies, in vivo human data have been unable to replicate in vitro predictions (Leber and Knauff, 1976;Piscitelli et al, 2002;DiCenzo et al, 2003;Gurley et al, 2004Gurley et al, , 2006aGurley et al, ,b, 2008Mills et al, 2005;van Erp et al, 2005;Fuhr et al, 2007;Rao et al, 2007;Deng et al, 2008). In a recent report, an in vitro study utilizing human liver microsomes evaluated a number of individual flavonolignans as potential P450 inhibitors and identified silybin B as the most potent inhibitor of CYP2C9 with an IC 50 value of 8.2 mM, followed by silybin A at 18 mM (Brantley et al, 2010). Isosilybin A and isosilybin B were noted to be much weaker CYP2C9 inhibitors with IC 50 values of 74 mM and .100 mM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Isosilybin A and isosilybin B were noted to be much weaker CYP2C9 inhibitors with IC 50 values of 74 mM and .100 mM, respectively. Brantley et al (2010) noted that there is precedent for some silymarin extracts formulated to provide significantly enhanced bioavailability (i.e., silibinin-phosphatidylcholine complex) to produce systemic concentrations of silibinin (i.e., combined silybin A and silybin B) between 5 and 75 mM (Flaig et al, 2007;Brantley et al, 2010). However, a previous dose escalation study assessing the pharmacokinetics of the formulation used in the present study produced silybin B plasma concentrations over an order of magnitude less than even the lowest concentration reported in the study by Flaig et al (2007) (Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%